2017
DOI: 10.1155/2017/1293201
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Promotes Self-Renewal and Tumorigenicity of Malignant Melanoma Initiating Cells

Abstract: Recent studies have indicated that therapeutic antibodies targeting PD-L1 show remarkable efficacy in clinical trials in multiple tumors and that a melanoma cell-intrinsic PD-1: PD-L1 axis promotes tumor growth. However, few studies have shown tumorintrinsic PD-L1 effects in malignant melanoma initiating cells (MMICs). Here, we aim to determine the possible regulatory effects of PD-L1 on MMICs. The ALDEFLUOR kit was used to identify ALDH + MMICs. Flow cytometry was used to examine the expression of PD-L1 on AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…By increasing expression of apoptosis-related genes, HIF1α usually exhibits a carcinogenic effect in tumor growth, such as in human salivary adenoid cystic carcinoma 22. The antiapoptotic effect of PD-L1, as well as its indicative function of poor prognosis, has been confirmed in tumors,12,23,24 offering a novel insight into developing effective targeted therapies. In the present study, we, for the first time, identified PD-L1 as a downstream target of HIF1α in repressing apoptosis of FTC in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By increasing expression of apoptosis-related genes, HIF1α usually exhibits a carcinogenic effect in tumor growth, such as in human salivary adenoid cystic carcinoma 22. The antiapoptotic effect of PD-L1, as well as its indicative function of poor prognosis, has been confirmed in tumors,12,23,24 offering a novel insight into developing effective targeted therapies. In the present study, we, for the first time, identified PD-L1 as a downstream target of HIF1α in repressing apoptosis of FTC in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PD-L1 overexpression acted as a useful prognostic marker for aggressive FTC and correlated with a great risk of FTC recurrence 10,11. In melanoma cell lines, blocking PD-L1 impairs tumor sphere formation and promotes apoptosis of sphere cells 12. However, the influence of PD-L1 on FTC cell apoptosis has not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several teams reported that independent of immune function, PD-L1 regulated cell growth, proliferation, apoptosis, autophagy, migration and invasion in various cancers including ovarian cancer, melanoma, and pancreatic cancer via modulating PI3K/Akt/mTOR signaling pathway (Clark et al, 2016; Zhao et al, 2017). Additionally, PD-L1 promotes self-renewal and tumorigenicity of malignant melanoma initiating cells (Zheng et al, 2017), as well as embryonic stem cell transcriptional factors octamer-binding transcription factor 4 (OCT4) and Nanog expression dependent on PI3K/Akt activation and B lymphoma Mo-MLV insertion region 1 homolog (BMI1) expression in PI3K/Akt independent manner in breast cancer stem cells (Almozyan et al, 2017). Both evidence suggest the tumor-intrinsic role of PD-L1 in modulating signal transduction and the PD-L1's oncogenic/ tumorigenic role in certain cancers.…”
Section: The Oncogenic Roles Of Endogenous Pd-l1 As a Signaling Proteinmentioning
confidence: 99%
“…Conversely, knockdown of PD-L1 in MOST-1 cells downregulated expression of anti-apoptotic genes (BCL2 and MCL1) [ 33 ] and silencing of PD-L1 in colorectal cancer cell line and gastric cancer cell lines was associated with an increased apoptotic index [ 50 , 51 ]. In addition, PD-L1 was shown to inhibit the apoptosis of malignant melanoma initiating cells and could contribute to maintaining the stem cell-like properties of these cells [ 56 ]. PD-L1 has also been shown to sustain stem cell-like features in breast cancer cells [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increased motility and invasiveness was shown in melanoma cell lines expressing PD-L1 [ 58 ]. PD-L1 was also shown to induce tumor formation in malignant melanoma initiating cells [ 56 ].…”
Section: Introductionmentioning
confidence: 99%